EKSISTENSI SANKSI ADAT VEAR HARTA MASYARAKAT ADAT KEI DALAM PRAKTIK PERADILAN PIDANA - Tallaut, Lambertus Josua; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Kei community's Sasa Sor Fit law is the same as the national criminal law. Both contain offenses and sanctions for perpetrators who violate them. If the Criminal Code has the popular criminal sanction of imprisonment, then Sasa Sor Fit has the customary sanction of Vear Harta. The dialectic between customary law and criminal law in criminal justice practice will be determined by the judge who hears the case to determine whether the existence of the Vear Harta customary sanctions is maintained in criminal justice practice. The problem in this research is How the Existence of Customary Sanctions for the Property of Kei Indigenous Peoples in Criminal Justice Practices. The type of research is normative, with the data used is secondary data obtained from primary legal materials and secondary legal materials using the literature study method and data analysis using descriptive methods. analytically by drawing conclusions deductively, the existence of customary law is recognized by the state through the Constitution Article 18B paragraph (2). Law enforcement also recognizes customary law which is embodied in the Judicial Power Law. The Larvul Ngabal customary law is one of the customary laws that still exists today in the Kei tribal community. Sasa sor fir Kei criminal law recognizes the Vear Harta customary sanction as the only sanction given to perpetrators who violate sasa sor fit. The dialectic between customary sanctions and criminal justice practices occurs in the Tual District Court Decision Number 35/Pid.B/2019/PN.Tul. The offense of murder, which is also regulated in the sasa sor fit, requires the defendant to fulfill the customary sanctions of vear property to the victim's family and fulfill them. In its considerations, the panel of judges considered wealth as a reason for mitigating the crime which ensures that the existence of the customary law of the Kei indigenous people is maintained.Keywords: Customary Sanctions Vear Harta, Kei Indigenous People, Criminal Justice